COMPLICATIONS OF PROSTHETICS WITH CLASP PROSTHESES WITH LOCK FASTENERS (American Journal of Pedagogical and Educational Research, 2023)
The development of alternative dental services allowed patients to choose between public dental care and private clinics. Many patients suffer from partial tooth loss at a relatively young age. Restoration of various defects with clasp and microprostheses using lock fasteners is one of the alternatives to standard treatment. At the same time, the use of fixed and removable dentures with lock fasteners of modern manufacturers requires the training of doctors and dental technicians, the availability of appropriate equipment for precision casting in foundry laboratories, compliance with manufacturing technology and the correct choice of the type of lock fastening in accordance with the features of the defect of the dentition. The practical use of lock fasteners during dental treatment is associated with a sufficient number of complications caused by medical errors. So, in the domestic literature there is only one message about errors in prosthetics of teeth using lock fasteners. Particular issues related to improving the quality of the therapeutic and diagnostic process in orthopedic dentistry were also considered. The analysis of domestic and foreign literature shows that currently in the practice of orthopedic dentistry there is no unified and formulated classification of errors and complications in prosthetics with the use of lock fasteners (attachments). There is also no documentation on all stages of orthopedic treatment using this type of composite structures. In addition, as practice shows, there is a problem of conflict situations in orthopedic dentistry during prosthetics using lock fasteners, the problem of clinical and professional assessment of medical errors and complications has not been studied, algorithms for their solution have not been developed. Therefore, an attempt was made to study the causes of medical errors and complications in orthopedic treatment using lock fasteners in patients with partial absence of teeth and, based on the results obtained, to increase the effectiveness of orthopedic treatment. Along with this, the influence of medical and legal literacy of orthopedic dentists on the resolution of conflict situations in the provision of this type of treatment was studied.